PENGARUH INVESTMENT OPPORTUNITY SET (IOS) PADA KEBIJAKAN DIVIDEN TUNAI DENGAN UMUR PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Sari, Ni Luh Putu Puspita; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
This research is aimed to examine the impact of IOS on cash devidend policy with firm age as moderating variable. Population in this research is the public companies which are listed at Indonesian Stock Exchange year 2006-2011. Sample is determined using purposive sampling technique. All of samples are grouping based on corporate life cycle stages as three big groups are: growth, mature, and decline.Hypothesis is tested for each corporate life cycle stages with moderated regression analisys methode. This research results that on the growth, IOS affect positively towards cash dividend policy. On the other hand, on the mature and decline stage IOS affect positively towards cash dividend policy but not significant. On the growth, mature, and decline stage, has no capability to moderate the relationship between IOS with cash dividend policy. Firm age on the decline stage is independent variable that affect positively significant towards cash dividend policy.
Keywords: IOS, cash dividend policy, firm age, and corporate cycle stages